Peran Pemerintah dalam Pengembangan Objek Wisata Pulau Camba-cambang Kabupaten Pangkep - Nurdalwah Makkasau; Rosmini Maru; Sukri Nyompa (UNM Geographic Journal, 2020)
This study aims to determine: 1) What is the role of local governments in the development of facilities and infrastructure. 2) What are the government's obstacles in developing tourism objects. 3) How is the management of natural tourism objects on Camba-cambang Island. The informants in this study were the Pangkep Regency Tourism Office, tourism object managers, workers, and the community around the tourist attraction. Data collection is done by using observation, interview, and documentation techniques. Data were analyzed descriptively qualitatively. The results showed that the development of facilities and infrastructure built by the government such as villas, gasebos, toilets, children's games, prayer rooms, places of sale, and infrastructure such as accessibility, generators, security infrastructure. 2) the obstacles experienced by the government in development are funds in the development of Camba Island tourism objects, the amount of which is uncertain, every year depending on regional income every year and plus the current covid-19 virus outbreak. 3) The management of the Camba-cambang Island tourist attraction is managed by the Pangkep Regency Tourism Office and its workforce, namely the people around Camba-cambang Island who come from Saugi Island who work in the Pangkep Regency government and are assigned as Camba-cambang Island workers.